Dimerization of SLX4 contributes to functioning of the SLX4-nuclease complex - Yin, Jinhu (Nucleic Acids Res, 2016)
The Fanconi anemia protein SLX4 assembles a genome and telomere maintenance toolkit, consisting of the nucleases SLX1, MUS81 and XPF. Although it is known that SLX4 acts as a scaffold for building this complex, the molecular basis underlying this function of SLX4 remains unclear. Here, we report that functioning of SLX4 is dependent on its dimerization via an oligomerization motif called the BTB domain. We solved the crystal structure of the SLX4(BTB) dimer, identifying key contacts (F681 and F708) that mediate dimerization. Disruption of BTB dimerization abrogates nuclear foci formation and telomeric localization of not only SLX4 but also of its associated nucleases. Furthermore, dimerization-deficient SLX4 mutants cause defective cellular response to DNA interstrand crosslinking agent and telomere maintenance, underscoring the contribution of BTB domain-mediated dimerization of SLX4 in genome and telomere maintenance.